Pregnancy rates in dairy cattle after three different, timed, breeding protocols - Cartmill, J. A.; El-Zarkouny, S. Z.; Lamb, G. C.; Stevenson, Jeffrey S. (Kansas Agricultural Experiment Station and Cooperative Extension Service, 2011)
Synchronizing ovulation enables dairy producers to inseminate cows by appointment rather than after detected estrus. Three different, timed artificial insemination protocols using different combinations of prostaglandin F2alpha and gonadotropin-releasing hormone were used to synchronize ovulation in 702 lactating Holstein cows. Cyclicity, pregnancy rate, and embryonic survival rate from each treatment were compared. Our results indicate that all three treatments produced acceptable pregnancy rates in first lactation cows. However, for cows in their second or greater lactation, the treatment using prostaglandin F2alpha 12 days before the Ovsynch protocol improved pregnancy rates more than the other two.
Keywords: Dairy; Ovsynch protocol; Pregnancy rates; Timed a.i.